Acid‐base disorders in sick goats and their association with mortality: A simplified strong ion difference approach. (3rd November 2020) - Gomez, Diego E.; Bedford, Sofia; Darby, Shannon; Palmisano, Megan; MacKay, Robert J.; Renaud, David L.
Abstract: Objectives: To investigate the acid‐base status of sick goats using the simplified strong ion difference ( s SID) approach, to establish the quantitative contribution of s SID variables to changes in blood pH and HCO3 − and to determine whether clinical, acid‐base, and biochemical variables on admission are associated with the mortality of sick goats. Animals: One hundred forty‐three sick goats. Methods: Retrospective study. Calculated s SID variables included SID using 6 electrolytes unmeasured strong ions (USI) and the total nonvolatile buffer ion concentration in plasma (Atot ). The relationship between measured blood pH and HCO3 −, and the s SID variables was examined using forward stepwise linear regression. Cox proportional hazard models were constructed to assess associations between potential predictor variables and mortality of goats during hospitalization. Results: Hypocapnia, hypokalemia, hyperchloremia, hyperlactatemia, and hyperproteinemia were common abnormalities identified in sick goats. Respiratory alkalosis, strong ion acidosis, and Atot acidosis were acid‐base disorders frequently encountered in sick goats. In sick goats, the s SID variables explained 97% and 100% of the changes in blood pH and HCO3 −, respectively. The results indicated that changes in the respiratory rate (<16 respirations per minute), USI, and pH at admission were associated with increased hazard of hospital mortality in sick goats. Conclusions and Clinical Importance: The s SID approach is a useful methodology to quantify acid‐base disorders in goats and to determine the mechanisms of their development. Clinicians should consider calculation of USI in sick goats as part of the battery of information required to establish prognosis.